2023
DOI: 10.1136/bmj.p1001
|View full text |Cite
|
Sign up to set email alerts
|

What is the future for covid drugs and treatments?

Abstract: Mun-Keat Looi reports on where research is focused and what’s missing from the covid treatment pipeline

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…But as drug resistance is an ever growing worry, combination treatments seem a likely avenue for immediate exploration 14. One small scale trial has found that a combination of remdesivir and nirmatrelvir-ritonavir with monoclonal antibodies induced a good clinical response in immunocompromised patients with prolonged or relapsed covid-19.…”
Section: What’s the Future Of Covid Treatments For Immunocompromised ...mentioning
confidence: 99%
“…But as drug resistance is an ever growing worry, combination treatments seem a likely avenue for immediate exploration 14. One small scale trial has found that a combination of remdesivir and nirmatrelvir-ritonavir with monoclonal antibodies induced a good clinical response in immunocompromised patients with prolonged or relapsed covid-19.…”
Section: What’s the Future Of Covid Treatments For Immunocompromised ...mentioning
confidence: 99%